2020
DOI: 10.1159/000511160
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in COVID-19 Patients: An Inner City Hospital Experience and Policy Implications

Abstract: Background: Although diffuse alveolar damage and respiratory failure are the key features of coronavirus disease 2019 (COVID-19), the involvement of other organs such as the kidney has also been reported. The reports of the incidence of acute kidney injury (AKI) in COVID-19 patients vary widely. In this study, we report our unique experience with AKI in COVID-19 patients in a low socioeconomic and predominantly ethnic minority group and provide its incidence, risk factors, and prognosis to expand the current u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
82
1
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 22 publications
(36 reference statements)
17
82
1
10
Order By: Relevance
“…Previous reports showed that kidney injury was associated with a poor prognosis among patients with COVID-19 [ 8 10 ]. A recent study involving 469 COVID-19 patients in USA revealed that AKI was an independent risk factor for in-hospital mortality [ 36 ]. A meta-analysis including 40 studies and 24,527 COVID-19 patients also demonstrated that AKI is associated with higher risk of mortality [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that kidney injury was associated with a poor prognosis among patients with COVID-19 [ 8 10 ]. A recent study involving 469 COVID-19 patients in USA revealed that AKI was an independent risk factor for in-hospital mortality [ 36 ]. A meta-analysis including 40 studies and 24,527 COVID-19 patients also demonstrated that AKI is associated with higher risk of mortality [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 [ 177 ] Cohort study AKI 416 China 64 205M&211F 8 (1.92%) Zheng et al. 2020 [ 4 ] Retrospective AKI 555 China 52 269M&286F 29 (6%) Russo et al., 2020 [ 178 ] Retrospective AKI 777 Northern Italy 70 59%M&41%F 176 (22.6%) Zahid et al., 2020 [ 179 ] Retrospective cohort study AKI 469 USA 66 268M&201F 128 (27.3%) Richardson et al., 2020 [ 180 ] Case series AKI 2634 USA NA NA 523 (22.2%) Hong et al., 2020 [ 181 ] Retrospective AKI 98 South Korea 55.4 38M&60F 9 (9.2%) Cheruiyot et al. , 2020 [ 5 ] Systematic review & meta-analysis AKI 5832 - - - 1730 (29.66%) Fu et al., 2020 [ 182 ] Systematic review and meta-analysis AKI 49048 - - - 5152 (10.50%) Robbins-Juarez et al., 2020 [ 183 ] Systematic review and meta-analysis AKI 13137 - - - 2233 (17%) Lazzeri et al., 2...…”
Section: Introductionmentioning
confidence: 99%
“…In some of these patients, even if they not diagnosed with AKI at admission, during the hospitalization they could be gradually worsened and diagnosed as AKI [10]. According to the recent literature, AKI incidence in hospitalized COVID-19 patients ranges from 8% to 22% [11].…”
Section: Discussionmentioning
confidence: 99%